Melhoria contínua da qualidade no processo de produção da camada Back-end de sistemas web em arquitetura REST - SAKAMOTO, Mário (2018)
Considering that in the literature observed there are no reports of a web tool of quality management that offers solutions for the evaluation of continuous quality improvement in the production process of the Back-end layer of web systems in REST architecture. The objective of this work was to develop a tool that manages functionality tests on access points of the Back-end layer through analysis of the response status of the HTTP communication protocol to evaluate the impact of the implementation of a production process based on the philosophy of Zero Defect of Philip Bayard Crosby, verifying the improvement of quality in an "initial level" software factory according to the CMMI. Database-related failures collected during factory production tests were analyzed using Statistical Process Control techniques for the validation of process control, measuring the upper and lower control limits by analyzing the mean number of related nonconformities to failures per unit of samples of variable size. For the development of the web tool of quality management were use programming languages and free use markup, such as HTML, CSS, JavaScript and PHP, as well as the use of relational database with the help of the MySql manager. As a result, the production process based on Crosby's philosophy was described and implemented in the organization of a factory, the web tool was developed and used, and a reduction of more than 90% in the percentage of nonconformities related to the failures identified in the after 60 days of use.